The Questionnaire of Intention to Help in VAW Cases (QIHVC): Development and preliminary results - Ferrer-Perez, Victoria A.; Sánchez-Prada, Andrés; Bosch-Fiol, Esperanza; Delgado-Alvarez, Carmen; Vázquez-González, Leila I.; Nardi-Rodriguez, Ainara (Frontiers in Psychology, 2023)
Violence against women is a worldwide social and health problem of epidemic proportions. This violence is preventable, and bystander programs are one of the possible preventative strategies. The main purpose of this research was to develop a tool that, by applying a contrastive methodology for its application in different forms of violence (forms of gender-based violence, such as intimate partner violence against women, sexual harassment at work, and street harassment, and common violence, such as a robbery), would allow measuring the probability of occurrence of bystander response in the face of these types of violence with good evidence of content validity. Firstly (Study 1), an initial version of a measure tool, the Questionnaire of Intention to Help in VAW Cases (QIHVC), was developed; secondly (Study 2), a Delphi (modified) study was carried out to obtain valid, content-based evidence; and finally, (Study 3) a pilot study was carried out to evaluate the appropriate functioning of the QIHVC and, if required, to make any necessary adjustments. The main result is the development of a set of case scenarios and a questionnaire related to its content which constitutes the QIHVC and, in its initial approximation, seems to constitute an adequate and sensible tool to capture the differences between the characterizations of common violence and VAW and in the possible response of bystanders in the face of such violence.